Evaluasi Kebijakan Perencanaan Pembangunan Pendidikan Daerah: Penilaian Ketercapaian Standar Pelayanan Minimal (SPM) Menggunakan Model CIPP - Disson Muhammad Fauzi (Sekolah Pascasarjana Universitas Muhammadiyah Prof. DR. Hamka bekerjasama dengan Himpunan Evaluasi Pendidikan Indonesia (HEPI)., 2025)
Purpose: To evaluate the effectiveness of regional educational development planning and the fulfillment of Minimum Service Standards (SPM) in South Jakarta, addressing underlying service quality disparities.Design/methodology/approach: This qualitative case study employed the CIPP evaluation model. Data were collected in 2025 via in-depth interviews, structured observations, and document reviews involving 15 key informants (planners, principals, supervisors) across the local Education Agency.Findings: While quantitative SPM targets were administratively met, the evaluation revealed severe input inequalities regarding digital facilities and compliance-driven bureaucratic processes. This polarized educational outcomes, specifically hindering the equitable distribution of numeracy literacy between elite and marginalized schools.Practical implications: Compels policymakers to precisely reallocate budgets towards adaptive learning technologies and shift administrative quality assurance instruments toward formative pedagogical supervision for educators.Originality/value: Pioneers a paradigm shift in SPM assessment from rudimentary